Hip muscle changes in femoroacetabular impingement: a systematic review and meta-analysis - Wen Zhang; Lei Chen; Peijian Tong (Journal of Orthopaedic Surgery and Research)
Abstract Background & aims Femoroacetabular impingement (FAI) is a common hip disorder characterized by abnormal contact between the femoral head and acetabulum, leading to pain, restricted mobility, and potential osteoarthritis. Despite its clinical significance, the role of periarticular muscle alterations in FAI progression remains controversial. This study aimed to systematically evaluate hip muscle strength alterations and their clinical implications in FAI through meta-analysis. Methods This systematic review and meta-analysis adhered to PRISMA and AMSTAR guidelines, analyzing five cross-sectional studies (118 FAI patients, 89 controls) to compare hip muscle strength (flexion, extension, abduction/adduction) and functional outcomes (e.g., iHOT-33, HAGOS). Risk of bias was assessed using the Newcastle-Ottawa Scale. Results FAI patients exhibited significantly reduced hip flexion (− 0.338 Nm/kg) and extension (− 0.379 Nm/kg) strength versus controls, with compensatory neuromuscular adaptations (e.g., preferential biceps femoris recruitment) and altered kinetic chains. Core muscle weakness and inconsistent fatigue patterns were also observed. Secondary outcomes lacked sufficient data for meta-analysis. Conclusion Muscle deficits in FAI are multifactorial, involving strength loss, maladaptive coordination, and kinetic chain disruptions. Targeted rehabilitation should integrate hip-centric and core stabilization exercises, but longitudinal studies are needed to validate therapeutic efficacy.